If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + -5p = -3p + -2 Reorder the terms: 14 + -5p = -2 + -3p Solving 14 + -5p = -2 + -3p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '3p' to each side of the equation. 14 + -5p + 3p = -2 + -3p + 3p Combine like terms: -5p + 3p = -2p 14 + -2p = -2 + -3p + 3p Combine like terms: -3p + 3p = 0 14 + -2p = -2 + 0 14 + -2p = -2 Add '-14' to each side of the equation. 14 + -14 + -2p = -2 + -14 Combine like terms: 14 + -14 = 0 0 + -2p = -2 + -14 -2p = -2 + -14 Combine like terms: -2 + -14 = -16 -2p = -16 Divide each side by '-2'. p = 8 Simplifying p = 8
| -5x+6=-4x+-7 | | 55x=110 | | asd=5 | | 2m^2+13m=24 | | 6x^2-10x-10=0 | | 26x-11-14x=3(4x-5)+4 | | 4x-29=-1x+-4 | | 14+5x=40 | | 6x-54=4x-20 | | -17x^2+13x+13=0 | | b^2+10b= | | 0=-17x^2+13x+13 | | -7=4+x/5 | | 92x+5=32x+17 | | 2x+2=4x-18 | | 23x=240 | | 11x+6y=18 | | 7+16x=80 | | 109-7x=20x+19 | | 2(-3x+3)-6x=-6 | | y/5+4=40.5 | | 23x=80 | | 9z-11=-65+3z | | (2y-5)(3y+7)= | | 0=-16t+vt+c | | 9z-11=65+3z | | (3x-2)(3x+2)=9x^2-18x+9-6(4-x)+12x | | x(12-104)=x(4-8) | | 2(-5x-7)+10x=-8 | | 8-7x=116-28x | | 2(q-7)+3=19 | | -4=2(x-6) |